Spatio-Temporal and Physiographical Study of the Abandoned Sutlej River: A Case of Jhangi Wala, Bahawalpur, Pakistan - Muhammad Javed Iqbal; M.M. Anwar; Muhammad Nasar U Minallah; Khalil-Ur- Rehman; Noor Hussain Chandio; K.V. Zakharov; Muhammad Mohsin; Muhammad Zafar Iqbal (Journal of Basic & Applied Sciences, 2018)
Rivers are the sign of prosperity, the hub of the economy and act as lifeline for the areas from where they flow. Rivers help in irrigation, ground water recharge, upgrading water quality, maintaining soil fertility, fostering forests. They also support in stabilizing industries, establishing cities and towns. Revirs are the sources of energy generation, enhancing tourism, managing wetlands, boosting fishing, avoiding desertification, droughts, famine and empowering people by providing employment opportunities. Rivers might stop flowing in any area through climatic changes, river piracy, and upper riparian monopoly. Sutlej River is now not flowing in Pakistan due to damming at its upper riparian (India) after the Indus Basin Water Treaty. In this paper, efforts are made to know about evolutionary processes through which Sutlej River passed from the old days and its present cruel and politicized abundance by the upper riparian. The main objective of the paper is to furnish a preliminary data base about Pakistan side (lower riparian) of the Sutlej River. Fact and figures used are mainly from the secondary sources and few primary sources and direct observations. By exploring and knowing about its spatial pattern, temporal evolutions, geographical, geological and physiographical changes and all the processes concerned to the river, it will be possible for us to educate our future generation about the conversion of past mighty and splendid Sutlej River into an abandoned River.